1979
DOI: 10.1071/ch9791841
|View full text |Cite
|
Sign up to set email alerts
|

Colouring Matters of Australian Plants. XXI. Naphthoxanthenones in the Haemodoraceae

Abstract: Two new pigments, haemofluorone A and haemofluorone B, have been isolated from the flowers of Macropidia fuliginosa Drum. and also from the root system of Phlebocarya ciliata R.Br. Spectroscopic analysis indicates the structures 5,8,9- and 8,9,11-trihydroxy-lH-naphtho[2,1,8-mna]xanthen-l-one. The former structure has been confirmed by a synthesis of the trimethyl ether by photochemical oxidative cyclization of 9-(3,4-dimethoxyphenyl)-6-hydroxy-2-methoxy-1H-phenalen-1-one.The parent chromophore, 1H-naphtho[2,1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Based on the above NMR data and combined with MS data (see Section 4), the structure of compound 21 was elucidated as 2,4-dihydroxy-9-(3,4-dihydroxyphenyl)-1H-phenalen-1-one. The other seven known compounds were determined by 1 H NMR and/or 2D NMR spectroscopy, mass spectrometry, and comparison with reported data as thyrsiflorin (1) (Dora et al, 1991), haemofluorone B (22) (Cooke and Dagley, 1979), anigorufone (10), hydroxyanigorufone (23), dihydroxyanigorufone (24) (Cooke and Thomas, 1975), 4-hydroxyanigorufone (25), and anigorootin (6) (Hö lscher and Schneider, 1999).…”
Section: Phenylphenalenones From Seedsmentioning
confidence: 99%
“…Based on the above NMR data and combined with MS data (see Section 4), the structure of compound 21 was elucidated as 2,4-dihydroxy-9-(3,4-dihydroxyphenyl)-1H-phenalen-1-one. The other seven known compounds were determined by 1 H NMR and/or 2D NMR spectroscopy, mass spectrometry, and comparison with reported data as thyrsiflorin (1) (Dora et al, 1991), haemofluorone B (22) (Cooke and Dagley, 1979), anigorufone (10), hydroxyanigorufone (23), dihydroxyanigorufone (24) (Cooke and Thomas, 1975), 4-hydroxyanigorufone (25), and anigorootin (6) (Hö lscher and Schneider, 1999).…”
Section: Phenylphenalenones From Seedsmentioning
confidence: 99%
“…2,17,[27][28][29]39,40 Off-line isolation and subsequent characterization of peak D (Figure 1) confirmed this component to be the new phenylphenalenone haemoxiphidone (8), which was isolated as an orange solid. This particular compound was concurrently isolated within the research group from a separate Haemodorum species.…”
mentioning
confidence: 57%
“…However, two reports have suggested that oxidative cyclization may be involved in converting phenylphenalenones to oxabenzochrysenones. 27,28 As part of continuing efforts to study the chemical diversity and ethnopharmacology of Australian plants, particularly of the family Haemodoraceae, the chemistry of Haemodorum spicatum R. Br. was investigated.…”
mentioning
confidence: 99%
“…[25][26][27][28] 9PPNs produce reactive oxygen species when exposed to UV and blue light [29][30][31][32] and produce secondary metabolites capable of absorbing light at longer wavelengths (Scheme 1 bottom). [33][34][35][36][37] The structural similarity between these metabolites and the NXs produced in the cyclization of 9PPNS, suggests a common mechanism of production. A major difference is the superior stability of the natural counterparts conferred by the rearomatization of the NX form by hydroxy-oxo tautomerization.…”
Section: Introductionmentioning
confidence: 95%